Greater decision-making competence is associated with greater expected-value sensitivity, but not overall risk taking: an examination of concurrent validity - Parker, Andrew M.; Weller, Joshua A. (Frontiers in Psychology, 2015)
Decision-making competence reflects individual differences in the susceptibility to decision-making errors, measured using tasks common from behavioral decision research (e.g., framing effects, under/overconfidence, following decision rules). Prior research demonstrates that those with higher decision-making competence report lower incidence of health-risking and antisocial behaviors, but there has been less focus on intermediate mechanisms that may impact real-world decisions, and, in particular, those implicated by normative models. Here we test the associations between measures of youth decision-making competence (Y-DMC) and one such mechanism, the degree to which individuals make choices consistent with maximizing expected value (EV). Using a task involving hypothetical gambles, we find that greater EV sensitivity is associated with greater Y-DMC. Higher Y-DMC scores are associated with (a) choosing risky options when expected value favors those options and (b) avoiding risky options when expected value favors a certain option. This relationship is stronger for gambles that involved potential losses. The results suggest that Y-DMC captures decision processes consistent with standard normative evaluations of risky decisions.